Dakwah Konstitusional Muhammadiyah: Antara Ideologi Islam Berkemajuan dan Komitmen Kebangsaan di Era Post Truth - Hanafiah, Yusuf; Humaidi, M. Nurul (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
As an Islamic movement, Muhammadiyah not only focuses on religious aspects, but also plays an active role in political and legal developments in Indonesia. This role is manifested in constitutional da'wah. This article aims to examine Muhammadiyah's constitutional da'wah strategy in responding to challenges in the post-truth era. In addition, this article also explains Muhammadiyah's efforts in maintaining a balance between Islamic values and the spirit of nationalism. This research is qualitative-descriptive with a library research approach by examining various relevant primary and secondary sources. Some of these sources include official documents of Muhammadiyah, decisions of the Constitutional Court, books, scientific journals, and credible online media. The results of this study show that 1) Muhammadiyah has shown its role in constitutional da'wah on the dynamics of law in Indonesia; 2) Muhammadiyah coordinates the Progressive Islamic Ideology and National Commitment in service to the Nation; and 3) Muhammadiyah faces the challenges of the post-truth era by prioritizing the main strategy of constitutional da'wah through strengthening literacy, continuous education, community empowerment, and optimization of social media in strengthening public opinion based on objective facts. The academic implication of this research is the formation of a conceptual framework for the constitutional da'wah approach in an effort to strengthen ideology and strengthen national commitment in the post-truth era.